CHARACTERISTICS OF CARDIAC ARRHYTHMIAS DETECTED BY 24-HOUR ECG HOLTER MONITORING IN BASEDOW’S DISEASE PATIENTS AT VIET TIEP FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives:To describe the characteristics of arrhythmias detected by 24-hour Holter electrocardiography and to assess the association between thyroid hormone indices and arrhythmias in patients with Graves’ disease at Viet Tiep Friendship Hospital during 2023–2024.Subjects and Methods:A total of 52 patients with confirmed Graves’ disease at Viet Tiep Friendship Hospital were included. This was a descriptive cross-sectional study using convenience sampling.Results:The mean age was 43.88 ± 15.39 years. The proportion of female patients (73.1%) was markedly higher than that of males (26.9%). Cardiovascular symptoms were common, with palpitations reported in 84.6% of patients, and tachycardia observed in 63.5%. The most common supraventricular arrhythmia was sinus tachycardia (51.9%). Atrial fibrillation was detected in 9.6% of patients by Holter monitoring, which was higher than that detected by standard electrocardiography (5.8%). The prevalence of supraventricular premature beats detected by Holter (21.2%) was also higher than that detected by standard ECG (3.8%).FT4 and TRAb levels showed weak positive linear correlations with heart rate (r = 0.16, p < 0.05; r = 0.20, p < 0.05), whereas TSH levels showed a weak negative correlation with heart rate (r = -0.11, p < 0.05).Conclusions:Twenty-four-hour Holter electrocardiography is a valuable tool for detecting arrhythmias in patients with Graves’ disease, particularly paroxysmal arrhythmias.
Keywords: Graves’ disease, arrhythmia, Holter electrocardiography